2021
DOI: 10.1111/add.15580
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of co‐occurring mental illness and substance use disorder and association with overdose: a linked data cohort study among residents of British Columbia, Canada

Abstract: Aims To estimate the treated prevalence of mental illness, substance use disorder (SUD) and dual diagnosis and the association between dual diagnosis and fatal and non‐fatal overdose among residents of British Columbia (BC), Canada. Design A retrospective cohort study using linked health, income assistance, corrections and death records. Setting British Columbia (BC), Canada. Participants A total of 921 346 BC residents (455 549 males and 465 797 females) aged 10 years and older. Measurements Hospital and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
1
15
0
1
Order By: Relevance
“…Prior studies have demonstrated that factors such as sex, age, comorbidities, substance use history, and concurrent prescriptions can contribute to risk of overdose and overdose mortality [24][25][26]. As such, a series of confounding Cox proportional hazard models were performed to evaluate the relationship between type of substance use and illicit drug toxicity death.…”
Section: Cox Proportional Hazards Modelsmentioning
confidence: 99%
“…Prior studies have demonstrated that factors such as sex, age, comorbidities, substance use history, and concurrent prescriptions can contribute to risk of overdose and overdose mortality [24][25][26]. As such, a series of confounding Cox proportional hazard models were performed to evaluate the relationship between type of substance use and illicit drug toxicity death.…”
Section: Cox Proportional Hazards Modelsmentioning
confidence: 99%
“…Similarly, mental health conditions are highly prevalent in persons with stimulant use disorders, with 35.7 to 41.6% having a lifetime history of major depression [ 8 ] and between 23 to 42% with lifetime history of PTSD [ 12 ]. Depressive symptoms along with other mental health conditions have been associated with nonfatal overdoses among individuals with SUD, drawing attention to the importance of early identification and treatment for these co-occurring conditions [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid depressive, trauma-related, and anxiety disorders, while less consistent risk factors for worse treatment outcomes ( 1 , 5 , 6 ), necessitate assessment and integrated approaches. These are especially urgent considering people with comorbid substance use and affective disorders are at high risk for fatal overdose people compared to those without comorbid disorders ( 7 ). While facilities providing methadone in the United States, formally called opioid treatment programs (OTPs), are required to provide substance use counseling or behavioral therapies in conjunction with medication treatment ( 8 ), there is no specific requirement for those counseling services to address co-occurring affective disorders ( 9 ).…”
Section: Introductionmentioning
confidence: 99%